Krasna Malanka - Sukholytkyy-Sobchuk, Dmytro (Ukraine, 2013)
Krasna Malanka tells the story of people from Romanian village Krasna on the territory of Ukraine getting prepared for the Malanka holiday. This holiday is a landmark event for everybody in Krasna, especially for young men because for them it is an initiation into adult life. Malanka is a carnival, a strange pagan show where everyone has his own part.
Verzio Film Festival Submission